Socio-demographic heterogeneity in the prevalence of COVID-19 during lockdown is associated with ethnicity and household size: Results from an observational cohort study. (August 2020) - Martin, Christopher A.; Jenkins, David R.; Minhas, Jatinder S.; Gray, Laura J.; Tang, Julian; Williams, Caroline; Sze, Shirley; Pan, Daniel; Jones, William; Verma, Raman; Knapp, Scott; Major, Rupert; et al.
Abstract: Background: Accumulating evidence indicates that COVID-19 causes adverse outcomes in ethnic minority groups. However, little is known about the impact of ethnicity and household size on acquiring infection with SARS-CoV-2. Methods: We undertook a retrospective cohort study, in Leicester (UK), of all individuals assessed for COVID-19 with polymerase chain reaction (PCR) testing at University Hospitals of Leicester NHS Trust between 1st March and 28th April 2020. We used logistic regression to identify sociodemographic, clinical and temporal factors associated with SARS-CoV-2 PCR positivity before/after lockdown. Findings: 971/4051 (24.0%) patients with suspected COVID-19 were found to be PCR positive for SARS-CoV-2. PCR positivity was more common amongst individuals from ethnic minortiy backgrounds than their White counterparts (White 20.0%, South Asian 37.5%, Black 36.1%, Other 32.2%; p <0.001 for all ethnic minority groups vs White). After adjustment, compared to White ethnicity, South Asian (aOR 2.44 95%CI 2.01, 2.97), Black (aOR 2.56 95%CI 1.71, 3.84) and Other (aOR 2.53 95%CI 1.74, 3.70) ethnicities were more likely to test positive, as were those with a larger estimated household size (aOR 1.06 95%CI 1.02, 1.11). We saw increasing proportions of positive tests in the three weeks post-lockdown amongst the ethnic minority, but not the White, cohort. Estimated household size was associated with PCR positivity after, but not before, lockdown (aOR 1.10 95%CI 1.03, 1.16). Interpretation: In individuals presenting with suspected COVID-19, those from ethnic minority communities and larger households had an increased likelihood of SARS-CoV-2 PCR positivity. Pandemic control measures may have more rapid impact on slowing viral transmission amongst those of White ethnicity compared to ethnic minority groups, Research is urgently required to understand the mechanisms underlying these disparities and whether public health interventions have differential effects on individuals from ethnic minority groups. Funding: NIHR